2018
DOI: 10.1016/j.entcom.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

More than skills: A novel matching proposal for multiplayer video games

Abstract: Multiplayer video games are high-involvement products with multiplatform and multiplayer characteristics which aim to enhance player retention by optimizing the matching of teams in accordance with their skills and attributes. However, relatively little academic research has been conducted into the ways in which player attributes can be used to optimize the formation of teams in multiplayer video games. Our study addresses this deficiency in the literature by analyzing a dataset from a popular online multiplay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…However, it is difficult to determine whether players prefer a fair match to an easy one. Some studies show that players spend more time and attempt more matches when they compete with equally skilled players [34] , [41] . However, Liu et al [34] found that players felt more enjoyment when competing with lower-skilled opponents, and Lomas et al [35] demonstrated that players were more engaged when they designed an easier educational game.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…However, it is difficult to determine whether players prefer a fair match to an easy one. Some studies show that players spend more time and attempt more matches when they compete with equally skilled players [34] , [41] . However, Liu et al [34] found that players felt more enjoyment when competing with lower-skilled opponents, and Lomas et al [35] demonstrated that players were more engaged when they designed an easier educational game.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…As a result, both traditional sport and video game organizations have developed systems to match players and teams based on player attributes (Stefani, 1997). This includes developing algorithms that use metrics to select players for teams in firstperson shooter games (Stroh-Maraun et al, 2018) and collegiate leagues, such as the National Association of Collegiate Esports Starleague which arranges esports competitions into tiers based on team rankings (Playfly Sports, 2023). This suggests that detecting in-game metrics that are important to the outcomes of video game matches can improve the identification and ranking of high-performing players.…”
Section: Player Performance In Sports Competitionsmentioning
confidence: 99%
“…Prior research focusing on player performance indicates that the psychological traits of team-based video game players can predict skill ratings, in addition to gaming experience (Bonny et al, 2020). Identifying attributes that are important to competitive video game team outcomes can enhance player satisfaction by selecting for these attributes (Stroh-Maraun et al, 2018). Similar to traditional physical sports, such as soccer and basketball, hundreds of thousands of individuals play team-based video games each day (Valve Corporation, 2020).…”
mentioning
confidence: 99%
“…Prugsamatz et al (2010), megállapították, hogy a videójátok piacán a fogyasztói hozzáállás szignifikáns meghatározója a vásárlási szándéknak, amely szerint megkülönböztettek "hardcore", azaz kemény-komoly játékosokat és "casual", azaz alkalmi játékosokat, a játszási idő és a kompetitív módban elért eredmények alapján. Stroh-Maraun et al (2018) leírták, hogy a többszemélyes videójátékok nagy tömegeket tudnak bevonzani termékeikkel, valamint fokozzák a fogyasztók pozitív hozzáállását azzal, hogy folyamatosan optimalizálják a "matchmaking"-et, azaz a számítógép által vezérelt játékostárs-keresőt. Ennek lényege, hogy a játékban elért eredmények alapján próbálják minél kiegyenlítettébe tenni a mérkőzéseket, azaz a szemben álló feleket azok játékban elért pontszámai, egyéni és csapat képességei szerint sorsolják össze.…”
Section: Marketing and Menedzsmentunclassified